Data in the cloud with OpenStack - Day, Eric (O'Reilly Media, 2011)
"The OpenStack project was launched last summer by Rackspace, NASA, and a number of other cloud technology leaders in an effort to build a fully-open cloud computing platform. It is a collection of scalable, standards-based projects currently consisting of OpenStack Compute and OpenStack Object Storage. This session will introduce the projects and describe how they can help manage your data."--Resource description page.